2009
DOI: 10.1002/cta.584
|View full text |Cite
|
Sign up to set email alerts
|

Current‐input OTRA Schmitt trigger with dual hysteresis modes

Abstract: SUMMARYA simple current-input Schmitt trigger is presented and implemented. It consists of one operational transresistance amplifier and a resistor. In addition, the circuit offers dual hysteresis mode operations within the same topology. The circuit operations are described. Experimental and simulation results are given to verify the theoretical analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…For the results as shown in Figs. 33 and 34, they are the square and triangular-waves when I B2 and I B3 = 20, 60 and 100 lA, respectively, it can be found that the output amplitudes of square and triangular-wave can be respectively tuned by I B2 and I B5 without affecting the frequency deviation, as analyzed in (30), (31) and (33). The last result is shown in Fig.…”
Section: Current-mode Triangular/square-wave Generatormentioning
confidence: 73%
See 1 more Smart Citation
“…For the results as shown in Figs. 33 and 34, they are the square and triangular-waves when I B2 and I B3 = 20, 60 and 100 lA, respectively, it can be found that the output amplitudes of square and triangular-wave can be respectively tuned by I B2 and I B5 without affecting the frequency deviation, as analyzed in (30), (31) and (33). The last result is shown in Fig.…”
Section: Current-mode Triangular/square-wave Generatormentioning
confidence: 73%
“…In 2008, the current-input Schmitt trigger based on OTRA [31] has been reported. It can operate as CCW and CW Schmitt triggers in the same topology.…”
Section: Introductionmentioning
confidence: 99%
“…It was first reported by Schmitt in 1938 [1]. A number of Schmitt trigger topologies based on various active elements such as operational amplifier (OP-AMP) [9], operational transconductance amplifier (OTA) [10], operational transresistance amplifier (OTRA) [11], secondgeneration current conveyor (CCII) [12,13], multiple-output current controlled current conveyor transconductance amplifier (MO-CCCCTA) [14], multiple-output current through transconductance amplifier (MO-CTTA) [15], multiple-output current controlled current differencing transconductance amplifier (MO-CCCDTA) [16], and differential difference current conveyor transconductance amplifier (DDCCTA) [17] have been so far reported in the available literature. Moreover, it is the fundamental block used in many applications such as a triangular/square wave generator [2][3][4], a monostable multivibrator [5,6], and a pulse width modulator [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of two OTAs in the configuration increases cost, chip area and power consumption. Recently Lo et al proposed a current-input Schmitt trigger employing an operational transresistance amplifier (OTRA), a floating resistor and a switch [16]. It was also previously used in a switch controllable bistable multivibrator and square/triangular wave generator [15,17].…”
mentioning
confidence: 99%
“…It was also previously used in a switch controllable bistable multivibrator and square/triangular wave generator [15,17]. The circuit in [16] provides clockwise (CW) or counterclockwise (CCW) hysteresis depending on the position of the switch but the output saturation voltages are determined by the rated voltages of the OTRA. A Schmitt trigger circuit with two positive-type CCIIs (CCII+s) and four resistors was proposed in [29].…”
mentioning
confidence: 99%